The interpretive contribution of the baseline serum cortisol concentration of the ACTH stimulation test in the diagnosis of pituitary dependent hyperadrenocorticism in dogs. (18th October 2018) - Nivy, Ran; Refsal, Kent R.; Ariel, Ella; Kuzi, Sharon; Yas‐Natan, Einat; Mazaki‐Tovi, Michal
Abstract : Background: Current recommendation for performing the ACTH stimulation test (ACTHST) for diagnosis of hyperadrenocorticism (HAC) advocates the collection of baseline serum cortisol concentration (BC), but no references for interpretation of its results exist. Objective: Evaluate the contribution of BC of the ACTHST to the diagnosis of HAC. Animals: Fifty‐four dogs were evaluated for suspected HAC at a referral hospital. Methods: Records of dogs that had been evaluated by ACTHST for suspected HAC were reviewed. Receiver operator characteristics (ROC) analyses were used to assess the performance of BC, post‐stimulation serum cortisol concentrations (PC), post‐to‐baseline cortisol concentration difference (DeltaC) and quotient (RatioC) for the diagnosis of HAC by comparing the area under the ROC curve (AUC) of PC to each of the other tests. Results: The AUC of PC (95% confidence interval [CI]: 0.92; 95% CI, 0.81‐0.98) was significantly higher than AUCs of BC (0.70; 95% CI, 0.56‐0.82; P = .01) and RatioC (0.55; 95% CI, 0.41‐0.69; P < .001), and was not significantly different from AUC of DeltaC (0.86; 95% CI, 0.74‐0.94; P = .09). An optimal cutoff value of 683 nmol/L (24.8 μg/dL) for PC yielded a sensitivity of 86% and a specificity of 94%, respectively, and a cutoff value of 718 nmol/L (26.0 μg/dL) yielded a specificity of 100% with of 81% sensitivity for the diagnosis of pituitary‐dependent HAC. Conclusion and Clinical Importance: The PC had good discriminatory ability for the diagnosis of HAC. It was comparable to DeltaC, whereas BC and RatioC were ineffective. Current recommendations to collect samples for BC appear redundant.